Time-resolved Mid-infrared Measurements of Hydrogen Peroxide in the Low-temperature Oxidation of Iso-octane in a Rapid Compression Machine. Issue 10 (27th July 2022) - Tanaka, Kotaro; Sugano, Shinya; Yokota, Naoya; Sakaida, Satoshi; Konno, Mitsuru; Nakamura, Hisashi
ABSTRACT: Time-resolved quantitative measurements of hydrogen peroxide (H2 O2 ) in the low-temperature oxidation of iso-octane in a rapid compression machine have been performed using mid-infrared absorption spectroscopy. H2 O2 was detected in the 8-μm region, wherein H2 O2 has the strongest absorption band. Owing to the weak interference of the absorption of iso-octane and H2 O in the 8-μm region, H2 O and iso-octane were detected in the 1.4- and 3.5-μm region, respectively. The cross-sections of H2 O2 and H2 O were calculated using parameters in the HITRAN database, and the iso-octane cross-section was measured using a rapid compression machine in the temperature and pressure ranges of 417–700 K and 100–700 kPa, respectively. The time-resolved quantitative H2 O2 profiles in the low-temperature oxidation of iso-octane at 0.77 MPa, 642 and 660 K, and an equivalence ratio of 1.0 were successfully obtained. The H2 O and iso-octane profiles were also obtained using this measurement method; the simultaneous measurements of the quantitative time profiles of multi-species in the low-temperature oxidation of fuels are also novel. Under experimental conditions, H2 O2 was formed during the low-temperature oxidation of iso-octane, and its concentration gradually increased between the end of the low-temperature oxidation and start of the high-temperature oxidation. The calculated H2 O2 profiles obtained using the latest chemical kinetic model of iso-octane showed the same tendency as the experimental profiles.